A 20 year experience in the management of non-tubal ectopic pregnancies in a tertiary hospital - a retrospective review - Theodora Hei Tung Lai; Jennifer Ka Yee Ko; Hung Yu Ernest Ng (BMC, 2024)
Abstract Background Non-tubal ectopic pregnancies account for < 10% of all ectopic pregnancies. Due to its rarity and wide variation in clinical practice, there is no guideline or consensus for its management. We reported our 20-year experience in the management of non-tubal ectopic pregnancies in a tertiary hospital. Methods This is a retrospective review of all women admitted for non-tubal ectopic pregnancies from January 2003 to December 2022 in a tertiary hospital. Women with non-tubal ectopic pregnancies diagnosed by ultrasound or operation were included for analysis. Results Within the study period, 180 women were diagnosed to have non-tubal ectopic pregnancies at a mean gestation of 6.8 weeks. 16.7% (30/180) were conceived via assisted reproduction. Medical treatment was the first-line management option for 81 women, of which 75 (92.1%) women received intralesional methotrexate administered under transvaginal ultrasound guidance. The success rate of intralesional methotrexate ranges from 76.5% to 92.3%. Intralesional methotrexate was successful even in cases with a positive fetal pulsation or with high human chorionic gonadotrophin levels up to 252605U/L. Twenty seven women were managed expectantly and 40 underwent surgery. Nine (11.1%), two (6.1%), and one (2.3%) women required surgery due to massive or recurrent bleeding following medical, expectant, or surgical treatment. Hysterotomy and uterine artery embolization were necessary to control bleeding in one Caesarean scar and one cervical pregnancy. Conclusions Intralesional methotrexate is more effective than systemic methotrexate and should be considered as first line medical treatment for non-tubal ectopic pregnancies. It has a high success rate in the management of unruptured non-tubal ectopic pregnancies even in the presence of fetal pulsations or high human chorionic gonadotrophin levels, but patients may require a prolonged period of monitoring. Close surveillance and readily available surgery were required due to the risk of heavy post-procedural intra-abdominal bleeding.